(untitled) (El-Wahat Journal for Research and Studies, 2016)
This paper evinces the organic form in T. S. Eliot’s The Waste Land. Though the poem is always considered as fragmented, it constitutes a unified whole. The poem consummates a marriage between form and content. Eliot’s poetic form resonates with modern existence that is fragmented. His personal experience also has a direct bearing on his style and mode of composition. The form is in tune with the reality of the poet’s psychological crisis and the outside shattered reality. Keywords – Fragmentation, The Waste Land, T. S. Eliot, Organic form, Psychological crisis, Unity.